Emotional homework: a systematic literature review of patients’ intersession experiences. - Stewart, Sally; Schröder, Thomas (American Psychological Association, 2015)
Patients’ processing of therapy between sessions can be planned and deliberate (homework) or spontaneous and incidental (intersession experiences). Aiming to inform clinical practice and future research, this review synthesizes empirical findings relating to intersession experiences, including their types, prevalence, and associations with patient characteristics, therapeutic processes, and outcomes. Searches of electronic databases identified 781 journal articles, 14 met the inclusion criteria of investigating adult psychotherapy patients’ unplanned between-session experiences relating to their therapy and therapist, a further 4 were identified through hand searches and contact with authors. All 18 articles included in the review were written in either English or German language, 17 used quantitative and 1 qualitative methods. Their methodological quality was assessed using tools developed for the purpose of this review. Most patients report a range of intersession experiences, including recreating therapeutic dialogue, imagining interactions, images and dreams. Intensity and type were associated with patient personality, diagnosis, phase of therapy, alliance and outcome. Study limitations included small sample sizes, the exploratory nature of some designs, and the limited generalizability of results. Clinical implications include the potential of intersession experiences to provide information about the therapeutic relationship, and their association to treatment outcomes and possible post-therapy gains.